To find which expression is equivalent to \(-3x - 5\), we can simplify each of the given options.
-
For \(-1 + (x - 4x) + 6\): \[ -1 + (x - 4x) + 6 = -1 - 3x + 6 = -3x + 5 \] This does not equal \(-3x - 5\).
-
For \((-4x - 6) + (2 + 5x)\): \[ (-4x - 6) + (2 + 5x) = -4x - 6 + 2 + 5x = (5x - 4x) + (-6 + 2) = x - 4 \] This does not equal \(-3x - 5\).
-
For \(-1 + 3x - (2x + 6)\): \[ -1 + 3x - (2x + 6) = -1 + 3x - 2x - 6 = x - 7 \] This does not equal \(-3x - 5\).
-
For \((x - 7) + (2 - 4x)\): \[ (x - 7) + (2 - 4x) = x - 7 + 2 - 4x = (x - 4x) + (-7 + 2) = -3x - 5 \] This expression simplifies to \(-3x - 5\), which is equivalent.
So, the correct expression equivalent to \(-3x - 5\) is \((x - 7) + (2 - 4x)\).